(untitled) (Research, Society and Development, 2020)
This paper presents the construction of a virtual wheelchair simulator. The use of assistive technologies aims to achieve a level of access to mobility for people with disabilities, such as people with low mobility. In this sense, simulators are developed with the aim of providing real-life situations, so that users can experience the same situation over and over again and overcome it in the best possible way. In this context, a virtual simulator was developed that can be adapted to several different situations according to the need, being composed of three scenarios of the day to day, in which were inserted some difficulties encountered by users of electric wheelchairs. The work was developed using the research methodology known as project dissertation, since it was proposed and developed the virtual environment for the wheelchair driving.